Analysis of the Impact of a Passive Interest in Sport on Student Lifestyle - Głowacki, Dominik (Analiza wpływu biernego zainteresowania sportem na tryb życia studentów, 2025)
Aim: The aim of the study was to determine the impact of a passive interest in sport on student lifestyle. Particular attention was given to analysing the relationship between the consumption of sports-related content and health behaviour, as well as attitudes toward physical activity. Methodology: Data were collected using a custom-designed survey questionnaire administered to 258 university students. The data analysis employed the chi-square independence test, correspondence analysis, and classification trees. Results: The study demonstrated that an interest in sport contributes to a healthier lifestyle among students, primarily by inspiring physical activity. Watching sports broadcasts and attending sports events as spectators proved to be significant determinants of a healthy lifestyle. A statistically significant, albeit weak, correlation between gender and level of interest in sport was also observed. Implications and recommendations: The findings suggest the need to promote the positive behavioural models exhibited by athletes, as these may motivate young individuals to adopt healthier lifestyles. It is also recommended to expand educational and media initiatives that encourage physical activity, especially among young people. Originality/value: This study provides new empirical data on the impact of the passive participation in sports culture on the daily health-related choices of young adults. It fills a gap in the literature regarding the social aspects of sports consumption and its influence on lifestyle behaviour.
Econometrics = Ekonometria, 2025, Vol. 29, No. 3, s. 30-43
Keywords: sport; correspondence analysis; chi-squared independence test; classification trees; healthy lifestyle; analiza korespondencji; test niezależności chi-kwadrat; drzewa klasyfikacyjne; zdrowy tryb życia